Predictors of Functional Outcome in Patients With Bipolar Disorder: Effects of Cognitive Psychoeducational Group Therapy After 12 Months - Sachs, Gabriele; Berg, Andrea; Jagsch, Reinhold; Lenz, Gerhard; Erfurth, Andreas (Frontiers in Psychiatry, 2020)
Background: Cognitive deficits are known as a core feature in bipolar disorder. Persisting neurocognitive impairment is associated with low psychosocial functioning. The aim of this study was to identify potential cognitive, clinical and treatment-dependent predictors for functional impairment, symptom severity and early recurrence in bipolar patients, as well as to analyze neurocognitive performance compared to healthy controls. Methods: 43 remitted bipolar patients and 40 healthy controls were assessed with a neurocognitive battery testing specifically attention, memory, verbal fluency and executive functions. In a randomized controlled trial, remitted patients were assigned to two treatment conditions as add-on to state-of-the-art pharmacotherapy: cognitive psychoeducational group therapy over 14 weeks or treatment-as-usual. At 12 months after therapy, functional impairment and severity of symptoms were assessed. Results: Compared to healthy controls, bipolar patients showed lower performance in executive function (perseverative errors p<0.01, categories correct p<0.001), sustained attention (total hits p<0.001), verbal learning (delayed recall p<0.001) and verbal fluency (p-words p<0.002). Cognitive psychoeducational group therapy and attention predicted occupational functioning with a hit ratio of 87.5%. Verbal memory recall was found to be a predictor for symptom severity (hit ratio 86.8%). Recurrence in the follow-up period was predicted by premorbid IQ and by years of education (hit ratio 77.8%). Limitations: Limitations of the present study result mainly from a small sample size. The extent of cognitive impairment appears to impact occupational disability, clinical outcome as well as recurrence rate. This result must be interpreted with caution because statistical analysis failed to show higher significance. Conclusions: Bipolar patients benefit from cognitive psychoeducational group therapy in the domain of occupational life. Deficits in sustained attention have an impact on occupational impairment. Implications for treatment strategies are discussed. Further evaluation in larger studies is needed.